2006
DOI: 10.1038/sj.bjc.6602979
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent chemotherapy (carboplatin, paclitaxel, etoposide) and involved-field radiotherapy in limited stage small cell lung cancer: a Dutch multicenter phase II study

Abstract: To improve the prognosis of limited stage small cell lung cancer (LS-SCLC) the addition of concurrent thoracic radiotherapy to a platinum-containing regimen is important. In the Netherlands, we initiated a multicenter, phase II study, of the combination of four cycles of carboplatin (AUC 5), paclitaxel (200 mg m À2) and etoposide (2 Â 50 mg orally for 5 days) combined with 45 Gy (daily fractions of 1.8 Gy). The radiation was given to the involved field and concurrently with the second and third chemotherapy cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(44 citation statements)
references
References 29 publications
1
41
0
2
Order By: Relevance
“…This rate is in accordance with our previous study (11%) which had the same up-front PCI treatment design [12]. In most other studies, the rate of brain recurrence was higher (30-40%) [11,[20][21][22]. In these studies, PCI was given to the patients with at least partial response after the end of the RCHT.…”
Section: Discussionsupporting
confidence: 90%
“…This rate is in accordance with our previous study (11%) which had the same up-front PCI treatment design [12]. In most other studies, the rate of brain recurrence was higher (30-40%) [11,[20][21][22]. In these studies, PCI was given to the patients with at least partial response after the end of the RCHT.…”
Section: Discussionsupporting
confidence: 90%
“…Several phase II trials have investigated the role of carboplatin and etoposide with concurrent TRT [53,54], and a retrospective review has revealed outcomes similar to those with cisplatin-based therapy [55]. However, phase III data comparing the efficacy of carboplatin with that of cisplatin in LS-SCLC are lacking and phase III data from carboplatin-based chemoradiotherapy are limited.…”
Section: Chemotherapy and Targeted Agents In Ls-sclcmentioning
confidence: 99%
“…We have updated our analysis of failure patterns in patients with limited-stage SCLC who were treated in our phase II study of involved-field irradiation during the second and third cycles of carboplatin, paclitaxel and etoposide (Baas et al, 2006). Of the 36 patients, isolated out-of-field nodal failures were only seen in two patients, one of whom developed an ipsilateral supraclavicular nodal recurrence after 10 months and the other developed a recurrence in the left hilar region after 18 months follow-up.…”
mentioning
confidence: 99%